(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Abstract. Modern realities of conducting agribusiness require a review of the methodology and organization of accounting for the costs of growing plant products. Traditional methods of accounting organization, which were adapted to a stable taxation system and uniform approaches to a set of expenditure items recommended by methodical recommendations for the agricultural industry, can today be considered as a genesis. Special adjustments to the organization of cost accounting are made under the conditions of martial law. This applies to economic subjects of agribusiness located in temporarily occupied territories, in territories liberated from occupation, in those located near hostilities, and those located in the free territories of our country. The special conditions of the martial law caused the redistribution of costs related to energy carriers, human resources, technical support of technological processes, crop insurance processes, the formation of transfer prices and the reflection in accounting of other specific costs and losses. The methods of accounting organization proposed in the article relate to the clarification of the provisions of the accounting policy regarding the list of cost items, the distribution of general production costs, the closing of the accounts of auxiliary productions and the determination of the full cost of crop production for the purposes of management accounting. The results of the study are relevant for agribusiness in view of the influence of the organization of plant production cost accounting on the formation of indicators of current activity, and indicators as a result of the process of selling these products. Indicators that are basic in the process of making managerial decisions will depend on the chosen method of organization of cost accounting. The accountant’s professional judgment has a significant impact on the choice of cost accounting methodology. Our own approach to the stages of development of the cost accounting methodology is based precisely on professional judgment as a priority in the preparation and justification of the information source for making management decisions. From cost accounting as a basis for calculating the cost of production to cost management taking into account the paradigm of sustainable development and institutional economics. All stages strengthened the role of professional judgment in the preparation of accounting information and the formation of accounting policy. The publication also considers the development of the theory of professional judgment in the context of interdisciplinary communication, in particular, economics, management, psychology. The global principles of management accounting are designed to unify integral thinking to strengthen the performance management system. In our opinion, standardization and unification are not priorities for management accounting methodology. Global principles can serve as certain recommendations for companies seeking development. This will be relevant for our domestic enterprises and organizations, which are already working on the development of strategies for the development of the country in the post-war period.